Integrasi Model Hujan-Aliran Dan Sistem Informasi Geografis (Studi Kasus DAS Katingan Provinsi Kalimantan Tengah) - Yusrianti, Destia Fitri; Nomeritae; Saputra, Raden Haryo (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
The Katingan watershed in Central Kalimantan Province, Indonesia, has experienced land use changes that have led to a reduction in the groundwater recharge areas. This study aims to examine the hydrological response of the Katingan watershed due to land cover changes by simulating the discharge of the Katingan River in Kasongan using the Arc-SWAT model integrated with Geographic Information System or GIS. The calibration results showed that the dominant physical parameters influencing the model were CN2 and ALPHA_BF. The CN2 value increased from 80 in 2013 to 83 in 2022, indicating a decrease in recharge areas and an increase in surface runoff volume. Meanwhile, the ALPHA_BF value remained 1 for all calibration years, indicating no significant changes in groundwater volume. The best-performing model was found for the calibration and validation years 2022 and 2023, indicating that land cover changes had a significant impact on the hydrological response of the Katingan watershed